An innovative stiffened I-shaped damper to improve the behavior of the concentrically braced frames - Hasan Nayel, Israa; Khaleel Nayel, Waleed; Ghamari, Ali; Putra Jaya, Ramadhansyah (Institution of Structural Engineers, 2024)
The Concentrically Braced Frames (CBFs) are prone to buckling under cyclic loads, which causes their degradation in energy absorption. Using steel dampers is an economical and efficient solution to improve their performance. Therefore, in this paper, an innovative metallic damper is considered numerically and parametrically to enhance the behavior of the CBF system. Accordingly, an I-shaped shear damper (stiffened diagonally by stiffeners) directly attached to the diagonal member of the CBF is proposed and studied parametrically and numerically. Results indicated that adding the diagonal stiffeners considerably enhances the ultimate strength and stiffness. By increasing the stiffener’s thickness from 2.5 mm to 20 mm, the ultimate strength is enhanced by 1.47 to 4.5, 1.48 to 4.33, 1.43 to 3.81, 1.39 to 338, and 1.33 to 2.65 times respectively for models with ρ = 0.25, 0.18, 0.13, 0.11 and 0.09. Also, the overstrength ratio, Ω, was affected by the stiffener's thickness. Accordingly, by increasing stiffeners thickness, the Ω was enhanced by 11 % to 75 %. Since local bucking of the stiffeners affects the behavior of the proposed damper, to prevent the local buckling of the stiffeners, the ratio of length to thickness, λL, and ratio of wide to thickness, λb, was recommended as 30 < λb < 60 and 30 < λL < 80.